A study to evaluate a correlation between various Gray Scale parameters and period of gestation - Chakarvarty, Nancy; Srivastav, Kumkum; Khanduri, Sachin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Accurate prediction of the gestational age (GA) is very important in the management of obstetric patients for planning a timely and uneventful outcome. Fetuses with intrauterine growth restriction (IUGR) are at high risk for poor short- and long-term outcome. The present study was conducted with the aim to evaluate a correlation between various Gray Scale parameters and period of gestation. Methods: A total of 100 clinically suspected FGR subjects were enrolled for the present study. Women with singleton pregnancies with fundal height being less than the period of gestation by 4 weeks or more and certainty of last menstrual period with previous 3 menstrual cycles were included in the present study. Ultrasound examination both by Gray Scale USG carried out serially every three weeks starting from 30 weeks till delivery. Chi-square test was used to compare the proportions while Independent Samples "t"-test was used to compare the parametric variables in two groups. Receiver-Operator curve analysis was performed to find out appropriate cut-off points for prediction of FGR. Results: Diagnostic accuracy of TCD/AC ratio as a marker of FGR was found to be 77%, of HC/AC ratio was found to be 93% and FL/AC ratio was 59%. Conclusions: Among three gray scale parameters being assessed, HC/AC ratio at 36 weeks was observed to be having 98.5% sensitivity and 82.9% specificity, thus showing the highest diagnostic accuracy (93%). However, from the point of view of early detection, TCD/AC ratio was found to be most efficient with 81.5% sensitivity and 68.6% specificity and overall diagnostic accuracy of 77%. Precision of Grayscale findings at later stage (36 weeks) are higher.